2008
DOI: 10.1017/s1742758408093181
|View full text |Cite
|
Sign up to set email alerts
|

Parasitism of Bemisia tabaci (Homoptera: Aleyrodidae) by Eretmocerus mundus (Hymenoptera: Aphelinidae) on cassava

Abstract: Parasitism rates of Bemisia tabaci (Gennadius) and searching and oviposition behaviours of its parasitoid Eretmocerus mundus Mercet were compared on two cassava varieties: a glabrous variety, Nase 4 and a hirsute variety, MM97/0245 with c. 88 leaf hairs/cm 2 . Parasitism was assessed after potted plants of both varieties were exposed in open fields to natural infestation by B. tabaci and its natural enemy. For the behavioural studies, naive, less than 24-h-old females were individually observed on infested cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…For B. tabaci, variants have been distinguished based on host range (Abdullah et al 2006;Attique et al 2003;Bird and Brown 1998;Butler and Brown 1985;Brown 1990, 1991;Costa et al 1991a, b;Costa and Russell 1975;Legg 1994Osmondi et al 2005;Sseruwagi et al 2006;Servin-Villegas et al 2006;Simon et al 2003;Thompson 2003) life history traits Costa et al 1991b;Demichelis et al 2005;Viscarret et al 2003), and other evidence for phenotypic variation, including differential virus transmission, which influences the epidemiology of viral outbreaks and their control (Brown et al , 2004aBrown and Bird 1996;Legg et al , 2008. For B. tabaci, variants have been distinguished based on host range (Abdullah et al 2006;Attique et al 2003;Bird and Brown 1998;Butler and Brown 1985;Brown 1990, 1991;Costa et al 1991a, b;Costa and Russell 1975;Legg 1994Osmondi et al 2005;Sseruwagi et al 2006;Servin-Villegas et al 2006;Simon et al 2003;Thompson 2003) life history traits Costa et al 1991b;Demichelis et al 2005;Viscarret et al 2003), and other evidence for phenotypic variation, including differential virus transmission, which influences the epidemiology of viral outbreaks and their control (Brown et al , 2004aBrown and Bird 1996;Legg et al , 2008.…”
Section: Historical Underpinningsmentioning
confidence: 99%
See 2 more Smart Citations
“…For B. tabaci, variants have been distinguished based on host range (Abdullah et al 2006;Attique et al 2003;Bird and Brown 1998;Butler and Brown 1985;Brown 1990, 1991;Costa et al 1991a, b;Costa and Russell 1975;Legg 1994Osmondi et al 2005;Sseruwagi et al 2006;Servin-Villegas et al 2006;Simon et al 2003;Thompson 2003) life history traits Costa et al 1991b;Demichelis et al 2005;Viscarret et al 2003), and other evidence for phenotypic variation, including differential virus transmission, which influences the epidemiology of viral outbreaks and their control (Brown et al , 2004aBrown and Bird 1996;Legg et al , 2008. For B. tabaci, variants have been distinguished based on host range (Abdullah et al 2006;Attique et al 2003;Bird and Brown 1998;Butler and Brown 1985;Brown 1990, 1991;Costa et al 1991a, b;Costa and Russell 1975;Legg 1994Osmondi et al 2005;Sseruwagi et al 2006;Servin-Villegas et al 2006;Simon et al 2003;Thompson 2003) life history traits Costa et al 1991b;Demichelis et al 2005;Viscarret et al 2003), and other evidence for phenotypic variation, including differential virus transmission, which influences the epidemiology of viral outbreaks and their control (Brown et al , 2004aBrown and Bird 1996;Legg et al , 2008.…”
Section: Historical Underpinningsmentioning
confidence: 99%
“…The latter is thought to be a recent introduction that catalyzed the initiation of the severe cassava mosaic disease, which involves several virulent begomoviruses (Legg et al , 2008. The latter is thought to be a recent introduction that catalyzed the initiation of the severe cassava mosaic disease, which involves several virulent begomoviruses (Legg et al , 2008.…”
Section: Allopatrymentioning
confidence: 99%
See 1 more Smart Citation
“…However, neonicotinoids are applied to Bt cotton for controlling whiteflies, and this resulted in the selection of resistant Q-biotype of B. tabaci [54,63]. A balanced approach for vector management would be the natural enemies of B. tabaci [103]. Although effective sources of resistance have been identified for non-Bemisia whitefly species in Latin America [17] and have suggested that these are less effective against African B. tabaci, [84,85].…”
Section: Vector Managementmentioning
confidence: 99%
“…Otim et al [48] suggested an urgent need to develop a balanced approach to CMD/CBSD/vector management, which can combine the deployment of CMD/CBSD/whitefly-resistant cultivars and alternative control methods, such as the use of B. tabaci natural enemies. Although effective sources of resistance have been identified for non-Bemisia whitefly species in Latin America [49], preliminary results suggest that these are less effective against African B. tabaci, and further research into alternative sources of resistance to B. tabaci is required [50][51].…”
Section: Iii24 Vector Managementmentioning
confidence: 99%